A contemporary justice perspective on dual ladders for R&D professionals. Issue 5 (12th February 2016) - Hoffmann, Patrick; Hoegl, Martin; Muethel, Miriam; Weiss, Matthias
Abstract : Research and development (R&D) professionals play a key role in companies' innovation performance. Whereas prior research has indicated the potential benefits of dual ladder career systems to retain and motivate R&D professionals, there is a lack of knowledge regarding the design properties of dual ladders that facilitate such positive effects. The purpose of this study is to address this research gap by exploring how organizations can design dual ladders to enhance R&D professionals' organizational commitment and career satisfaction. Drawing on contemporary justice theory, we point to two factors integral for the successful application of dual ladders: the perceived equality of the technical ladder and the transparency of the dual ladder. These factors are related to R&D professionals' organizational commitment and career satisfaction. Furthermore, this study investigates whether these relationships are moderated by R&D professionals' age and self‐directedness in career management as well as firm size. The hypotheses are tested in a cross‐level study with 9 heads of R&D departments, 32 human resource managers, and 382 R&D professionals from 32 organizations. Based on the analyses, this study finds positive relationships between the perceived equality and the transparency of the dual ladder with R&D professionals' organizational commitment and career satisfaction. In addition, the findings show that the effects of the perceived equality of the technical ladder on R&D professionals' career satisfaction are weaker at high levels of self‐directed career management. The study contributes by developing theory on the consequences of dual ladders' design properties and moderating influences thereon. Thus, this research has implications for the literature on innovation management by expanding the knowledge on the interplay between career management and the human side of innovation.